Almond oil for patients with hyperlipidemia: A randomized open-label controlled clinical trial. (February 2019) - Zibaeenezhad, Mohammad Javad; Ostovan, Parham; Mosavat, Seyed Hamdollah; Zamirian, Mahmood; Attar, Armin
Highlights: Coronary artery disease (CAD) currently accounts for nearly half of the non-communicable diseases. Hyperlipidemia was reported as an important risk factor of CAD. Frequent consumption of nuts was demonstrated to have an association with reduction in the incidence of CAD and be associated with less atherogenic plasma lipid profile. This study was undertaken to assess the effect of almond oil on lipid profile in hyperlipidemic patients Regular almond oil consumption could improve total cholesterol and LDL levels but did not significantly affect the triglyceride and HDL. Abstract: Background: Cardiovascular diseases currently account for nearly half of non-communicable diseases. It was shown that enjoying a handful of nuts every day can significantly reduce the risk of developing heart diseases as they contain a variety of nutrients and other bioactive substances contributing to lowering the risk of heart diseases and controlling the cholesterol. The aim of this study was to determine the effect of almond oil on the lipid profile of patients with hyperlipidemia. Methods: Ninety-seven patients were divided into the intervention (n = 49) and control (n = 48) groups. The intervention group received 10 ml of almond oil two times daily for 30 days. There was no intervention for the control group. The serum lipoproteins were measured before and after the study. Results: The total cholesterol and LDL levels decreased significantly in the intervention group (treatment difference = -16.12 ± 26.16, P = 0.009; treatment difference = -20.88 ± 18.4, p < 0.001 respectively). But regular almond oil consumption did not significantly affect the triglyceride and HDL in this sample of hyperlipidemic patients. Conclusion: Consumption of almond could reduce the total cholesterol and LDL in dyslipidemic patients.